Free thyroxine measurement by analogue immunoassay and equilibrium dialysis in dogs with non-thyroidal illness. (October 2022) - Bennaim, Michael; Shiel, Robert E.; Evans, Helen; Mooney, Carmel T.
Abstract: Objectives: Measurement of free T4 by analogue immunoassay (fT4a) is popular but its ability to differentiate hypothyroidism from non-thyroidal illness (NTI) is unclear. The aims were to assess fT4a concentrations in dogs with NTI and to explore diagnostic agreement with total T4 and free T4 measured by equilibrium dialysis (fT4d). Methods: fT4a was measured in dogs classified with mild, moderate and severe NTI. Total T4 and fT4d were measured in a subgroup of these dogs. Results: 146 dogs were included of which 84, 35 and 27 had mild, moderate and severe NTI, respectively. Median (range) fT4a concentrations (pmol/L) were significantly lower ( P  = 0.023 and P  < 0.001) in dogs with severe (3.86 (3.86–23.60)) compared with moderate (11.10 (3.86–34.70)) and mild (15.25 (3.86–48.60)) NTI. Overall, 49 (33.6% [95% CI, 26.4–41.6]) dogs had low fT4a concentration. All thyroid hormones were measured in 74 dogs. Agreement was substantial between total T4 and fT4a (κ=0.79 [95% CI, 0.65–0.92]) and fT4a and fT4d (κ =0.63 [95% CI, 0.47-0.79]) but moderate between total T4 and fT4d (κ=0.49 [95% CI, 0.32–0.66]). Of 42 dogs with low total T4 concentration, five (11.9% [95% CI, 5.19–24.99]) and 18 (42.9% [95% CI, 29.12–57.80]) had fT4a and fT4d within reference interval, respectively. Conclusions and clinical importance: fT4a and fT4d cannot be used interchangeably. Measurement of fT4a provides limited further diagnostic information over measurement of total T4 in dogs with NTI. This study raises concerns regarding the ability of fT4a to differentiate NTI from hypothyroidism in dogs with low total T4 concentrations. Highlights: Free T4 concentration as measured by an analogue method is affected by the severity of nonthyroidal illnesses Free T4 concentration as measured by an analogue method and by equilibrium dialysis cannot be used interchangeably Free T4 as measured by an analogue method provides limited information over total T4 in dogs with nonthyroidal illnesses